2018
DOI: 10.1194/jlr.m083436
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea and effects of continuous positive airway pressure on triglyceride-rich lipoprotein metabolism

Abstract: This study aimed to explore lipoprotein metabolism in obstructive sleep apnea (OSA) and the effects of continuous positive airway pressure (CPAP). We studied 15 men with severe OSA [apnea-hypopnea index (AHI) ≥30 events/hour] and 12 age-, BMI-, and waist circumference-matched volunteers without OSA (AHI <5 events/hour). Carotid intima-media thickness (CIMT) was determined by a blind examiner. After 12 h fasting, a triglyceride-rich chylomicron-like emulsion, labeled with [C]cholesteryl oleate and [H]triolein, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 38 publications
4
19
0
Order By: Relevance
“…A recent study in OSA patients corroborates the previous results from rodents exposed to IH, showing a decreased lipolysis of triglyceride-rich lipoproteins in patients with severe OSA [66]. Furthermore, delayed triglyceride-rich lipoproteins clearance through adipose tissue lipoprotein lipase inhibition were associated with increased carotid intima-media thickness [66]. The majority of observational studies support a link between OSA and dyslipidaemia [64], while in a meta-regression analysis, apnoea-hypopnoea index had a significant effect on low density lipoprotein and triglycerides [67].…”
Section: Adipose Tissue and Ih: Insight From Rodent And Reductionist supporting
confidence: 88%
See 1 more Smart Citation
“…A recent study in OSA patients corroborates the previous results from rodents exposed to IH, showing a decreased lipolysis of triglyceride-rich lipoproteins in patients with severe OSA [66]. Furthermore, delayed triglyceride-rich lipoproteins clearance through adipose tissue lipoprotein lipase inhibition were associated with increased carotid intima-media thickness [66]. The majority of observational studies support a link between OSA and dyslipidaemia [64], while in a meta-regression analysis, apnoea-hypopnoea index had a significant effect on low density lipoprotein and triglycerides [67].…”
Section: Adipose Tissue and Ih: Insight From Rodent And Reductionist supporting
confidence: 88%
“…As previously described in rodents, IH results in an increase in metabolic dyslipidaemia in patients with OSA [65] favoured by upregulated triglycerides and phospholipids biosynthesis, and inhibited triglyceride uptake in the liver. A recent study in OSA patients corroborates the previous results from rodents exposed to IH, showing a decreased lipolysis of triglyceride-rich lipoproteins in patients with severe OSA [66]. Furthermore, delayed triglyceride-rich lipoproteins clearance through adipose tissue lipoprotein lipase inhibition were associated with increased carotid intima-media thickness [66].…”
Section: Adipose Tissue and Ih: Insight From Rodent And Reductionist supporting
confidence: 85%
“…Furthermore, the same group has recently shown that people with severe OSA exhibited delayed lipoprotein remnants removal as well as decreased lipolysis of TG rich particles. Both processes were positively correlated with the severity of IH and were enhanced by CPAP treatment [52]. Our data are also pointing in the same direction and highlighting the beneficial impact of MLS in the treatment of OSA.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, the same group has recently shown that people with severe OSA exhibited delayed lipoprotein remnants removal, as well as decreased lipolysis of TG-rich particles. Both processes were positively correlated with the severity of IH and were enhanced by CPAP treatment [ 55 ]. Our data also point in the same direction and highlight the beneficial impact of MLS in the treatment of OSA.…”
Section: Discussionmentioning
confidence: 99%